2015
DOI: 10.1039/c4em00439f
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of α-cypermethrin in soil in the presence of trace metals (Cu2+, Cd2+, Fe2+and Zn2+)

Abstract: The influence of trace metals (Cu(2+), Zn(2+), Cd(2+) and Fe(2+)) on the photodegradation of α-cypermethrin (α-CYM) in agricultural soil was studied. The soil samples were spiked with α-cypermethrin with/without the presence of metal ions, irradiated under a UV irradiation chamber for a regular period of time and analyzed by using HPLC. The dark control sterile and unsterile soil samples spiked with α-cypermethrin and selected trace metals were incubated for the same interval of time at 25 °C. The results obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…For example, Zn 2+ and Cu 2+ are known to reduce the dissipation of deltamethrin and cypermethrin in the soil but Fe promotes their dissipation rate (Yang et al., 2010) . Similarly, our previous studies have also reported the degradation of CLP, and a number of other pesticides in the presence of some metals (Rafique et al., 2016a, Rafique and Tariq, 2015). It is important to determine the metals that have pronounced influence on the photodegradation of pesticides but have minimal hazardous effect on the environment so that a strategy may be developed for safer remediation of these pesticides from the soil.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…For example, Zn 2+ and Cu 2+ are known to reduce the dissipation of deltamethrin and cypermethrin in the soil but Fe promotes their dissipation rate (Yang et al., 2010) . Similarly, our previous studies have also reported the degradation of CLP, and a number of other pesticides in the presence of some metals (Rafique et al., 2016a, Rafique and Tariq, 2015). It is important to determine the metals that have pronounced influence on the photodegradation of pesticides but have minimal hazardous effect on the environment so that a strategy may be developed for safer remediation of these pesticides from the soil.…”
Section: Introductionsupporting
confidence: 77%
“…2-a). Zinc has also been reported to enhance the photodegradation of α-cypermethrin in soil (Rafique and Tariq, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They not only influence the people involved in agriculture but also are carried to long distances because of their longer half-lives and entering the water bodies in the end [6, 7, 8, 9, 10]. This scenario is worsened in countries like Iran due to limited water resources and existing resources being polluted by the reckless and unnecessary use of the agrochemicals [11]. Therefore, developing a well-organized and cost-effective technology seems essential to remove these dangerous pollutants from waters and wastewaters completely.…”
Section: Introductionmentioning
confidence: 99%